2014
DOI: 10.1140/epjc/s10052-014-2970-8
|View full text |Cite
|
Sign up to set email alerts
|

Gauss–Bonnet coupling constant as a free thermodynamical variable and the associated criticality

Abstract: The thermodynamic phase space of GaussBonnet (GB) AdS black holes is extended, taking the inverse of the GB coupling constant as a new thermodynamic pressure P GB . We studied the critical behavior associated with P GB in the extended thermodynamic phase space at fixed cosmological constant and electric charge. The result shows that when the black holes are neutral, the associated critical points can only exist in five dimensional GB-AdS black holes with spherical topology, and the corresponding critical expon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(80 citation statements)
references
References 50 publications
5
74
0
Order By: Relevance
“…In these circumstances, the black hole mass known as an internal energy is replaced by enthalpy. Recently, the critical behavior of charged AdS black holes such as Reissner-Nordstrom-AdS and Kerr-Newman-AdS black holes has been investigated in the extended phase space (while the cosmological constant Λ is included as a thermodynamic variable) and in the canonical ensemble [24,25,42,43]. The critical behaviors are analogous to the liquid-gas phase transition in the Van der Waals fluid.…”
Section: Introductionmentioning
confidence: 99%
“…In these circumstances, the black hole mass known as an internal energy is replaced by enthalpy. Recently, the critical behavior of charged AdS black holes such as Reissner-Nordstrom-AdS and Kerr-Newman-AdS black holes has been investigated in the extended phase space (while the cosmological constant Λ is included as a thermodynamic variable) and in the canonical ensemble [24,25,42,43]. The critical behaviors are analogous to the liquid-gas phase transition in the Van der Waals fluid.…”
Section: Introductionmentioning
confidence: 99%
“…These geometrical area (entropy) bounds are also studied in Gauss-Bonnet gravity [47], where the Gauss-Bonnet coupling constant should also be treated as a thermodynamical variable (see, e.g. [42,[48][49][50][51][52]). Meanwhile, area bounds are modified by the constants of theory.…”
Section: Asymptotically Ads Black Holementioning
confidence: 99%
“…For a charged black hole with a spherical event horizon there are critical points, associated with large black/small black hole phase transitions, with mean field exponents [122]- [124].…”
Section: D−2mentioning
confidence: 99%
“…For D = 5 this can happen even when the black hole is electrically neutral but for D ≥ 6 there must be a non-zero charge [122]. In [125] it was found that, when the potential Φ is held fixed rather than the electric charge, the critical point persists only for D = 5.…”
Section: D−2mentioning
confidence: 99%